Transverse phase space mapping of relativistic electron beams using optical transition radiation - G. P. Le Sage; T. E. Cowan; R. B. Fiorito; D. W. Rule (Physical Review Special Topics. Accelerators and Beams, 1999)
Optical transition radiation (OTR) has proven to be a versatile and effective diagnostic for measuring the profile, divergence, and emittance of relativistic electron beams with a wide range of parameters. Diagnosis of the divergence of modern high brightness beams is especially well suited to OTR interference (OTRI) techniques, where multiple dielectric or metal foils are used to generate a spatially coherent interference pattern. Theoretical analysis of measured OTR and OTRI patterns allows precise measurement of electron beam emittance characteristics. Here we describe an extension of this technique to allow mapping of divergence characteristics as a function of transverse coordinates within a measured beam. We present the first experimental analysis of the transverse phase space of an electron beam using all optical techniques. Comparing an optically masked portion of the beam to the entire beam, we measure different angular spread and average direction of the particles. Direct measurement of the phase-space ellipse tilt angle has been demonstrated using this optical masking technique.